Konsekuensi Hukum Perusahaan Konglomerasi Dalam Aplikatif Monopoli Menimbulkan Eskalasi Pasar Persaingan Tidak Sehat - Akmal Dwi Prasyetio Setiady; Rani Apriani (Peneliti.net, 2023)
In the business world, fair competition must be implemented in all companies, whether it's an individual company or a conglomerate business, so that a free market occurs and does not harm each other. the motive is only to earn as much income as possible from the company owned, even though in the business law regulations it is stated that the act of market monopoly is a less commendable act because it is only profit-oriented and is detrimental to other business actors, as stated in the 1991 Law of the Republic of Indonesia concerning the Prohibition of Monopolistic Practices and Competition. unhealthy Article 4 paragraph (1) (1) Business actors are prohibited from entering into agreements with other business actors to jointly control the production and or marketing of goods and or services which may result in monopolistic practices and or unfair business competition which indicates the prohibition that business actors are prohibited from obtainin